Relevansi Kurikulum SMK dengan SKKNI Kompetensi Keahlian Teknik Instalasi Tenaga Listrik di Provinsi Aceh - Ghufran Ibnu Yasa; Hari Anna Lastya; Gunawan Iqbal (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
Based on the results of interviews with the vice principal of the curriculum section at one of the Vocational High Schools (SMK) of Aceh Province, it was found that the problem faced many SMK graduates who had not worked, whether they were not absorbed by DU/DI or do not worked in accordance with the majors in the school. This situation needs further analysis to improve the quality of graduates, including educational supporting components such as school infrastructure and curriculum documents. Regarding the curriculum, it is necessary analyzing the implementation of the curriculum and reflecting on its recent implementation. This study aims to determine the relevance of the curriculum implementation to the Indonesian National Employability Standards (SKKNI). This research is kind of quantitative research with using questionnaire as the instrument. The sample involved in this study included 11 electric power installation engineering teachers consisting of 4 teachers at SMKN 2 Banda Aceh, 3 teachers at SMKN Darul Kamal Aceh Besar and 4 teachers at SMKN 2 Meulaboh. The results showed that the level of relevance of curriculum implementation at SMKN 2 Banda Aceh with SKKNI 92% was in the very relevant category, at SMKN Darul Kamal 100% (very relevant category) and SMKN 2 Meulaboh 69% (relevant category). Finally, it can be concluded that the level of curriculum implementation relevancy with SKKNI in Aceh Province as 87% (very relevant category).